2021
DOI: 10.1021/acssuschemeng.1c07158
|View full text |Cite
|
Sign up to set email alerts
|

Insight on Performance Degradation of Phthalocyanine Cobalt-Based Gas Diffusion Cathode for Carbon Dioxide Electrochemical Reduction

Abstract: Phthalocyanine is a type of non-noble metal electrocatalyst that efficiently and selectively produces CO from CO2. Herein, we studied the durability of a cobalt phthalocynine (CoPc)-based gas diffusion electrode (GDE) in a flow cell. This is the first report on the degradation mechanism of the CoPc-based GDE for CO2 electrochemical reduction. Leaching of CoPc and demetalation of phthalocyanine are observed, and the interaction between CoPc and carbon black becomes weaker after a durability test. More seriously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Moreover, compared with other reported Co‐based catalysts in flow cell, the as‐prepared CoPc/S‐NHC shows outstanding performance (Figure 5e). [ 39–43 ] It is found that CoPc/S‐NHC has a very low reaction potential for CO 2 RR, with a FE CO of more than 90% at only −0.4 V (vs RHE). Notably, CoPc/S‐NHC achieves FE CO of 98.5% at −0.6 V (vs RHE), which is the maximum value of CoPc‐based catalysts in a flow cell as we know (Table S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, compared with other reported Co‐based catalysts in flow cell, the as‐prepared CoPc/S‐NHC shows outstanding performance (Figure 5e). [ 39–43 ] It is found that CoPc/S‐NHC has a very low reaction potential for CO 2 RR, with a FE CO of more than 90% at only −0.4 V (vs RHE). Notably, CoPc/S‐NHC achieves FE CO of 98.5% at −0.6 V (vs RHE), which is the maximum value of CoPc‐based catalysts in a flow cell as we know (Table S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The displacement inevitably leads to the so-called flooding of the CL, which results in increased HER and less eCO 2 RR. 1,19−24 Various strategies are proposed in the literature to address this issue, such as altering the composition of hydrophobic species in the MPL, 6,21,22,25 adding organic additives on the CL, 26,27 augmenting the amount and/or type of buffering species in the electrolyte, 28,29 increasing the (back) pressure at the gas side of the GDE, 2,30 etc. All of these measures will (in)directly restore the location of the TPB at the CL instead of within the bulk of the GDE, reversing the adverse effect of elevating the temperature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[32][33][34] Electrochemical stability, synthetic complexity and costs remain critical hurdles for molecular CO2 catalysts to truly compete with Ag-based electrolyzers in an industrial environment both in aqueous or gasfed systems. 35 Moreover, no molecular systems have yet shown increased CO-producing activity at current densities beyond 200 mA cm -2 -the starting point for industrially relevant CO2 electrolysis-under elongated time periods in industrially relevant cell concepts or have been tested in industry employed systems, involving elevated temperatures and diluted anolytes. 36 From our viewpoint, for a molecular electrocatalyst to truly achieve the transition to the applicable scale it must: a) achieve similar CO2R activities at current densities > 200 mA cm -2 to Ag-based electrolyzers, b) be cheap to produce via few scalable synthetic steps to allow for the production of m 2 -scale electrodes, and c) possess a robust ligand environment able to withstand the harsh conditions of CO2 electrolysis at elongated time scales.…”
Section: Introductionmentioning
confidence: 99%